A study on ankle traction and interferential therapy for the treatment of osteoarthritis of knee joint - ROOPA DESAI; C. V .JOHN FRANKLIN; MANISHA RATHI (International Journal of Pharma and Bio Sciences, 2017)
Osteoarthritis is a chronic degenerative disorder of multifactoral etiology characterized by loss of articular cartilage, hypertrophy of bone at the margins, subchondral sclerosis and range of biochemical and morphological alterations of the synovial membrane and joint capsule. 59 subjects, suffering from unilateral Osteoarthritis of knee joint participated in this experimental study. After considering inclusion and exclusion criteria, subjects were divided into 3 groups. Group A received Ankle Traction, Group B received Interferential Therapy and Group C received a combination of Ankle Traction and Interferential Therapy. All three groups were given exercises in common. The subjects were assessed on a modified Indian Version of WOMAC Index (CRD Pune Version) in English and Marathi languages. The subjects were assessed prior to the 1st day of the treatment session. Similar assessments were taken by the end of 1st week and 2nd week and scores were taken. With ‘t’ test, there was a significant improvement in the total WOMAC Score and its sub parameters of pain, stiffness and functional score in all 3 groups ( Gr. A- score 29.55 reduced to 12.95 , in Gr. B - score 31.3 reduced to 14.4 and in Gr. C – score 32.11 reduced to 13.79 ). Whereas ANOVA did not show significant difference in the pain, stiffness and functional score of WOMAC Index between all 3 groups. It was concluded that all three methods of treatment i.e Ankle Traction with exercises, Interferential Therapy with exercises and a combination of Ankle Traction and Interferential Therapy along with exercises are equally effective in the management of Osteoarthritis of knee joint.